Development of Interactive Learning Media Based on Classpoint in Argumentation Text for Class XI Senior High School Students - Anisa Putri Rahayu; Septyanti, Elvrin; Permatasari, Silvia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop interactive learning media based on ClassPoint in learning argumentation text for students of Class XI at Senior High School 2 Tambang. This research is motivated by students' low understanding of argumentation text, which is caused by teachers' limitations in providing interesting learning media and low student involvement in the learning process. Conventional method tends to be unable to meet the needs of 21st-century students who are familiar with technology and demand participatory learning. Therefore, ClassPoint-based interactive media was developed to improve students' understanding and active involvement. This study used a Research and Development (R&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 32 students of class XI at Senior High School 2 Tambang. Data collection techniques were conducted through interviews, questionnaires, and tests, with descriptive qualitative, quantitative, and descriptive statistical data analysis. The results reveal that the media developed was very valid according to material experts (93%), linguists (95%), and media experts (92%). The media is effective for student learning outcomes with an average posttest score of 85.22 and significance <0.001. The media practicality was also high according to students (92.19%), teachers (95.00%), and observers (93.75%). This research contributes to developing technology-based learning media and provides proper solutions to improve the quality of argumentation text learning in senior high schools.